Front Cover: Gallium(III) Corrole Complexes as Near‐Infrared Emitter – Synthesis, Computational and Photophysical Study (Eur. J. Org. Chem. 10/2021). Issue 10 (4th March 2021) - Haas, Michael; Krisch, Dominik; Gonglach, Sabrina; Bechmann, Matthias; Scharber, Markus C.; Ertl, Martin; Monkowius, Uwe; Schöfberger, Wolfgang
Abstract : The Cover Feature shows novel gallium(III)‐ethynyl corroles, which serve as a precursor for Sonogashira cross‐coupling reaction with aryliodides in a flow‐reactor system. Theoretical and photophysical studies reveal that the optical properties of such gallium(III)‐ethinylcorroles can be selectively tuned with different aryl‐substituents. As an example, the novel gallium(III)‐pyridine‐5, 10, 15‐pyrenylethynyl‐corrole complex exhibits a Soret‐band maximum at 510 nm and emission maximum at 740 nm with fluorescence quantum yields ΦF = 0.27 in aerated toluene solution. More information can be found in the Full Paper by W. Schöfberger et al.